Unveiling the Impact of Metacognition on Academic Achievement in Physical Education and Activity Settings: A Comprehensive Systematic Review and Meta-Analysis of Qualitative Insights - Bao L; Soh KG; Mohd Nasiruddin NJ; Xie H; Zhang J (Psychology Research and Behavior Management, 2024)
Lixia Bao,1,2 Kim Geok Soh,1 Nasnoor Juzaily Mohd Nasiruddin,3 Huijuan Xie,1 Junlong Zhang1 1Department of Sports Studies, Faculty of Educational Studies, Universiti Putra Malaysia, Serdang, Malaysia; 2Physical Education Department of Yuncheng University, Shanxi, People’s Republic of China; 3Department of Sports Studies, University of Malaya, Kuala Lumpur, MalaysiaCorrespondence: Lixia Bao, Zone 4 Off Jalan Stadium, Universiti Putra Malaysia, Serdang, 43400, Selangor, Tel +86 13834955653, Email gs62086@student.upm.edu.my Kim Geok Soh, Department of Sports Studies, University of Malaya, Serdang, Malaysia, Tel +60 193649715, Email kims@upm.edu.myPurpose: The purpose of this study is to unveil the impact of metacognition on academic achievement in physical education and activity settings by conducting a comprehensive systematic literature review with a meta-analysis of qualitative findings.Patients and Methods: Systematic searches identified English-language, peer-reviewed journal articles reporting the results of qualitative or mixed-methods studies of the emerging themes of metacognition on academic achievement in sports. PubMed, Web of Science, Scopus, ProQuest, and SPORTDiscus were searched from inception to June 2023.Results: Data from 20 studies were included in the review. Thematic meta-analysis identified descriptive themes: 1) Metacognitive performance during the learning process in different sports disciplines; 2) Domains of metacognitive skills related to academic performance; 3) Self-regulation strategies related to academic performance; 4) Influencing factors of metacognition; 5) Metacognitive interventions on motor learning and academic performance. Generate an analytical theme based on five descriptive themes.Conclusion: In-depth descriptions of the emerging themes related to metacognition and academic performance during motor learning were provided by different students and athletes. The conclusions reported in the study align with the theoretical models of metacognition. The research findings will provide strategies for physical education teachers, coaches, and trainers to enhance both physical and academic performance.Keywords: metacognitive skill, self-regulation learning, learning performance, executive function